Aging Markers in Equine Red Blood Cells - Kämpf, Sandra; Seiler, Elena; Bujok, Jolanta; Hofmann-Lehmann, Regina; Riond, Barbara; Makhro, Asya; Bogdanova, Anna (Frontiers in Physiology, 2019)
Detection of hematopoietic activity in horses is a challenge due to the lack of cells carrying reticulocyte markers such as RNA remnants or CD71 in the circulation. In this study we fractionated equine red cells according to their density and analyzed the cells forming low (L), medium (M) and high (H) density fractions for such marker of ageing as membrane loss, oxidation and alterations in the intracellular free Ca2+ levels. Cells forming L and M fraction were highly heterogeneous in projected areas and shapes and had higher propensity to swell in response to hypo-osmotic challenge than the cells from the H fraction. The densest cells were deprived of band 3 protein compared to the cells within L or M fraction. Furthermore, the equine red cells from the H fraction were hyper-oxidized compared to the cells within M and L fractions as follows from an increase in autofluorescence characteristic for oxidized damaged hemoglobin and from thiol oxidation as detected using monobrombimane. The lightest cells showed lower free thiol content compared to the red blood cells from the M fraction, but did not contain oxidized hemoglobin. Finally, the majority of red blood cells forming L, M and H fraction prominently differed from each other in intracellular free Ca2+ levels and its distribution within the cells. Based on the obtained findings we suggest that intraeryhtrocytic Ca2+ levels and its subcellular distribution, eosin-5-maleimide binding test for band 3 abundance, and autofluorescence of cells along with the changes in red blood cell indices, distribution width and creatine levels may become potential markers of regenerative erythropoiesis in horses. Validation of the power of these potential markers of red cell ageing is pending.